The reporting of studies conducted using observational routinely collected health data statement for pharmacoepidemiology (RECORD-PE). (14th November 2018) - Langan, Sinéad M; Schmidt, Sigrún AJ; Wing, Kevin; Ehrenstein, Vera; Nicholls, Stuart G; Filion, Kristian B; Klungel, Olaf; Petersen, Irene; Sorensen, Henrik T; Dixon, William G; Guttmann, Astrid; Harron, Katie; et al.
Abstract : In pharmacoepidemiology, routinely collected data from electronic health records (including primary care databases, registries, and administrative healthcare claims) are a resource for research evaluating the real world effectiveness and safety of medicines. Currently available guidelines for the reporting of research using non-randomised, routinely collected data—specifically the REporting of studies Conducted using Observational Routinely collected health Data (RECORD) and the Strengthening the Reporting of OBservational studies in Epidemiology (STROBE) statements—do not capture the complexity of pharmacoepidemiological research. We have therefore extended the RECORD statement to include reporting guidelines specific to pharmacoepidemiological research (RECORD-PE). This article includes the RECORD-PE checklist (also available on www.record-statement.org ) and explains each checklist item with examples of good reporting. We anticipate that increasing use of the RECORD-PE guidelines by researchers and endorsement and adherence by journal editors will improve the standards of reporting of pharmacoepidemiological research undertaken using routinely collected data. This improved transparency will benefit the research community, patient care, and ultimately improve public health.